Obesity prevalence, physical activity, and dietary practices among adults in Saudi Arabia - Alsulami, Salhah; Baig, Mukhtiar; Ahmad, Tauseef; Althagafi, Nouf; Hazzazi, Eman; Alsayed, Razan; Alghamdi, Majd; Almohammadi, Thikra (Frontiers in Public Health, 2023)
The current study evaluated obesity prevalence, physical activity, and dietary practices among Saudi adults in the Makkah region of the Kingdom Saudi Arabia (KSA). The current survey was accomplished between November 2021 and March 2022. A validated questionnaire, Arab Teens Lifestyle Study (ATLS), was used to evaluate all participants' physical activities, sedentary behaviours, and nutritional habits in addition to demographic data. A total of 2115 people (1238 [58.5%] women and 877 [41.5%] men) participated in this survey. Being overweight was prevalent in 32.8 percent of the population (41 percent of men and 28.9 percent of women), obesity was prevalent in 23 percent of the population (males 23.1 percent and females 24.2 percent). Obese people consumed more soft drinks, and overweight people did not consume enough vegetables (fresh/cooked). Obese people consumed fast food (e.g., burgers, sausage, pizza, or Arabic shawarma) over three times each week. The mean (SD) number of days of practice walking was 2.51(2.05) vs. 1.3 (1.87) (p<.001) for lean and obese individuals, respectively. In addition, individuals with normal BMI had more days of jogging, moderate and high-intensity exercise, dancing, and strength training than those with obesity. The odds of being obese increased with age (OR: 1.07; p<.001), in married people (OR: 1.43; p=.764), in males (OR: 2.16; p<.001), in participants earning less than 5000 SR and earning 10-15 thousand SR/month (OR: 2.36; P=.01). Obesity was inversely associated with moderate-intensity exercise (OR:.802; p=.009), and regular walking (OR:.685; CI:.624-.752; p<.001). Overweight and obesity were prevalent in 32.8% and 23% of the population, respectively. Sociodemographic factors associated with obesity. Focused intervention strategies are needed to overcome the obesity issue.